Analysis of technical efficiency and socio-economic factors influencing the development of smallholder oil palm plantations in Batanghari Regency, Indonesia - Yanuar Fitri; Saidin Nainggolan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah)
This study aims to analyze technical efficiency and the influence of socio-economic factors on the development of smallholder oil palm plantations. Data were collected using the Simple Random Sampling method, utilizing both primary and secondary data. The analytical methods employed include descriptive analysis and the Stochastic Frontier Production Function with the Maximum Likelihood Estimation (MLE) method. The results reveal that the average size of oil palm plantations is 3.9 hectares per farmer, with a productivity rate of 13,853 kg/ha. Production factors such as land area, NPK fertilizer, urea, and dolomite fertilizer significantly influence production, whereas labor and herbicides show no significant effects. The technical efficiency levels range from 0.81 to 0.95, with an average of 0.86, which is greater than the threshold of 0.62, indicating that oil palm plantations operate at a technically efficient level. Socio-economic factors, including land area and plantation distance, potentially increase technical inefficiency but have no statistically significant effect. Conversely, variables such as farming experience, access to technology, and active participation in farmer groups help reduce technical inefficiency. To promote the development of smallholder oil palm plantations, it is crucial to focus on enhancing technical efficiency, as it directly impacts productivity. Additionally, consideration of farmers' socio-economic conditions and external factors such as market prices and environmental conditions is essential.